The Analysis of Fund Accounting Benefits in Increasing the Effectiveness of Financial Report for Non for Profit Organization (Gereja Batak Karo Protestan Pontianak) - Barus, Carolinday B1034131002 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research is based on the problems of that every church has which is difficult to provide an effective financial report that will be easy to understand by all users of the financial statements especially in the financial statements of Gereja Batak Karo Protestan Pontianak. Fund accounting can help the financial reporting process become easier. Fund accounting can support the financial reporting process so that financial information obtained will be more qualified. The purpose of this study is to find out how effective the financial statements of GBKP Pontianak and know the benefits of fund accounting in improving the effectiveness of financial statements so that financial information obtained will be more effective as well. This is an analytic descriptive research which the data used is secondary data obtained directly from the church assembly. The data provided is called Musyawarah Sidi which contains all financial statements within a period in one year. Available financial statements consist of work programs, recapitulation of receipts and expenditures of categorical and sectors, ledgers, trial balances and church inventory lists. The results show that the Gereja Batak Karo Protestan Pontianak has applied the fund accounting to their financial reporting which is marked with the financial report focusing on the source and allocation of funds. Funds consist of continuous collections, and donations from donors, both internal and external which are needed at any given time. GBKP Pontianak has also implemented some fund accounting elements such as good human resources resources, have budget planning, transactions records and preparation of financial statements. In this case the financial statements GBKP Pontianak has several weaknesses such as no closing entries, and no depreciation in the recording the fixed assets. Therefore, GBKP should make some improvements in their financial reporting by applying the fund accounting elements further to create more effective financial statements.